Osteopenia in Premature Infants and Effect of Supplementation (Bangladesh Journal of Child Health, 2017)
Background: Despite advances in antenatal and prenatal care, incidence of preterm labor is still high. Osteopenia of prematurity is one of the common accompaniments or complications of surviving preterm babies. Most of the time this problem remains hidden, so is untreated by most of the physicians which leads to growth retardation, delayed bone maturation, fractures with minimal trauma and other complications in infancy.Objective: This study was an attempt to see osteopenia in preterm babies admitted in hospital and to see the effect of supplementation with calcium and phosphorus on those babies and to corelate serum calcium and phosphorus level with gestational age and bone density.Methods: A total 96 of preterm babies admitted in Dhaka Shishu (Children) Hospital (DSH) and Maternal & Child health Training Institute (MCHTI) of either sex were selected randomly during the period of January 2005 to June 2006. Venous blood was tested for serum calcium and phosphorus level and X-ray of lower limb to see bone density. All cases were given calcium 200 mg/kg/day and phosphorus 90 mg/kg/day with multivitamin drop of 6 drops/day up to 3 months of age.Result: Out of 96 preterm babies 27 had osteopenia with male preponderance [67%]. Gestational ages were between 28-32 weeks and in 78% cases weight were with 1000-1500 gm. Most of the mothers were 18-25 years and housewives. Initial mean serum calcium level was 1.66 mmol/l and phosphorus level was 1.58 mmol/l. After 3 months of supplementation, it was 2 mmol/l and 2.08 mmol/l respectively. Serum alkaline phosphatase was initially 736.6 and follow up level after 3 months was 353.14. Weight also increased, it was[mean] 3448 g whereas initial weight was 1277 gm.There was significant reduction of alkaline phosphatase during the 3 months [P < 0.05].Conclusion: Prevalence of osteopenia is high (28%) in premature infants. Less the gestational age more the chance of osteopenia. Calcium and Phosphorous supplementation has showed very good effect to achieve normal growth pattern.Bangladesh J Child Health 2015; VOL 39 (3) :135-140